2020
DOI: 10.1038/s41467-020-20617-y
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: The association between early career informal mentorship in academic collaborations and junior author performance

Abstract: This article has been retracted. Please see the retraction notice for more detail: https://doi.org/10.1038/s41467-020-20617-y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In 2020, computational social scientist Bedoor AlShebli at New York University Abu Dhabi and her colleagues published a nowretracted study in Nature Communications analysing the gender and seniority of 215 million authors on 222 million papers in several fields over 100 years. The team designated senior authors as 'mentors' to junior co-authors 11 .…”
Section: Mentorship's Gender Landscapementioning
confidence: 99%
“…In 2020, computational social scientist Bedoor AlShebli at New York University Abu Dhabi and her colleagues published a nowretracted study in Nature Communications analysing the gender and seniority of 215 million authors on 222 million papers in several fields over 100 years. The team designated senior authors as 'mentors' to junior co-authors 11 .…”
Section: Mentorship's Gender Landscapementioning
confidence: 99%
“…Finally, a worldwide study of 3 million senior-junior published research collaborations over a century across 10 scientific fields (physics, geology, chemistry, biology, computer science, engineering, materials science, medicine, psychology, economics) examined the later career benefits to junior scientists of co-authoring papers with senior scientists during their training years (AlShebli et al, 2020). The results indicated that senior female scientists were less productive later in their careers than senior male scientists when they collaborated with female versus male junior scientists.…”
Section: Tactic 4: Challenge Status Demarcationsmentioning
confidence: 99%
“…6 AlShebli et al 2020 did not account for how their dataset spanning "over a century of research" was biased and reflected the systemic barriers that women scientists have faced. 3 Throughout the 20th century, women scientists were given fewer resources and opportunities, resulting in under-valued and under-reported accomplishments. 14 Marginalization has been even worse for PEERs, whose participation and contributions have been further suppressed by white supremacy and colonialism; yet discussion of intersectionality was absent from AlShebli et al 2020.…”
Section: How Can We Make the Scientific Publication Process More Rigorous And Socially Just?mentioning
confidence: 99%
“…Last year, Nature Communications published a study that counters Nature Research 's commitments to diversity, equity, and inclusion (DEI) . 3 Journal decisions to publish articles like the now-retracted AlShebli et al 2020-which suggests that women scientists are less impactful mentors and mentees-are evidence of larger systemic failures and the enduring power of systems of oppression in science.…”
Section: Introductionmentioning
confidence: 99%